2015
DOI: 10.2527/jas.2015-8907
|View full text |Cite
|
Sign up to set email alerts
|

Use of pattern recognition techniques for early detection of morbidity in receiving feedlot cattle 1

Abstract: Two groups of cattle were used to develop (model data set: 384 heifers, 228 ± 22.7 kg BW, monitored over a 225-d feeding period) and to validate (naïve data set: 384 heifers, 322 ± 34.7 kg BW, monitored over a 142-d feeding period) the use of feeding behavior pattern recognition techniques to predict morbidity in newly arrived feedlot cattle. In the model data set, cattle were defined as morbid (MO) if they were removed from their pen to be treated due to visual observation of clinical signs of bovine respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The paper of Moya et al . (2015) is the only paper that addresses three different machine-learning techniques, reporting on supervised classification, unsupervised clustering and dimensionality reduction. The papers from Martinez-Ortiz et al .…”
Section: Resultsmentioning
confidence: 99%
“…The paper of Moya et al . (2015) is the only paper that addresses three different machine-learning techniques, reporting on supervised classification, unsupervised clustering and dimensionality reduction. The papers from Martinez-Ortiz et al .…”
Section: Resultsmentioning
confidence: 99%
“…Lukas et al (2008) reported preclinical reductions in DMI in dairy cows with mastitis and reductions in water intake associated with the febrile response. Using pattern recognition techniques, Moya et al (2015) reported that morbid cattle exhibit distinctive deviations in feeding behavior patterns prior to displaying overt clinical signs of BRD and can be differentiated from the feeding patterns of healthy cattle. Based on discrete survival time analysis of DMI and feeding behavior data, Wolfger et al (2015) reported that increases in DMI per meal, meal frequency and intermeal interval were associated with a decreased hazard for developing BRD up to 7 d prior to observed clinical signs of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted that have monitored changes in behavioral or physiological patterns of individual animals to predict the onset of disease. Other attempts at early identification have used hazard analyses (Wolfger et al, 2015), mean comparison (Sowell et al, 1999), logistic regression (Schaefer et al, 2007), and cluster analyses (Moya et al, 2015). There are also studies and commercial products available that have published results without clearly defining the method or described the algorithm that was used to predict BRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of SPC-model of BRD based on feed bunk attendance and head-down duration occurred 2.7 and 3.0 days prior to observed BRD diagnosis, with model accuracies of 87 and 89%, respectively. More recently, Moya et al (2015) used nonlinear data-mining analysis of feeding behavior data to develop pattern-recognition-based algorithms to predict morbidity events in beef cattle. When validated against a naive group of calves, they were able to correctly predict the health status of high-risk calves with a model accuracy of 79%.…”
Section: Precision Livestock Farmingmentioning
confidence: 99%